The Locations of (World) Literature - Orsini, Francesca,; Zecchini, Laetitia, (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
Location matters, for critics, readers and texts. This book explores the notion of location not simply as geographical, historical, or cultural context but as a standpoint, a position, an orientation, a necessarily partial and particular perspective, however ample it may be, from which writers represent and imagine their worlds. However, the constraint of location in the form of a reductive geographical marker has been felt most acutely by writers of the Global South. This book explores how modern and contemporary writers from Africa and South Asia consider their place in the world, in world literature, and in the wider geographical regions or national literary histories to which their work is identified with. What worlds do these literatures simultaneously inhabit and create? What networks do writers and institutions, specific genres and works of literature, but also circuits of readership, translation and publishing, produce? And what are the imagined or discrepant geographies, the different cosmopolitanisms, that may be invented in the process? This ground-up approach - from Lagos, Algier, Niamey, Addis Ababa or Allahabad; in English and in French but also in Swahili, Malayalam, Amharic, Urdu, Arabic, Persian, or Pulaar - can pluralize a map whose entanglements and complexities face the risk of being ironed out by reified conceptualizations of literature within global macro-systems.